ANDRAGOGI - Supriyati (Dwija Inspira: Jurnal Pendidikan Multi Perspektif, 2018)
The understanding of educators or facilitators in dealing with adults as students in the development of adult psychological conditions of course has its own significance. Understanding of such adult psychological conditions grew in a theory known as andragogy. Andragogy is a science that has a broad and deep dimension of learning theory and in how to teach adults. In learning, adults have a characteristic, principles and conditions in learning, from experience and awareness of their needs in learning, so as not to feel compelled in learning and in accordance with the needs and problems faced, so that, learning is sourced and oriented with the problem. The more mature a person is, the more matures of his academically or biologically according to life experience and the length of time travel. Some of the tasks done in Adult education, are teachers as facilitators, program developers (Developer Programs), managers (Administration) and as counselors (Counselors). Learning should be a need and awareness of the importance of science, motivation and responsibility as an adult capable of responsibility, and can develop itself and take an active role in the community environment. In order to the process of learning activities to take place eï¬€ectively and eï¬ƒciently, adult learning theory is not only known, but must be applicable in every teaching and learning activities and enhance the spirit of both formal and non formal learning activities.